ChemInform Abstract: Stereoselective Glycosylations by Nitrosyl Tetrafluoroborate‐Catalyzed Activation of Glycosyl Trichloroacetimidate Derivatives. Issue 4 (31st January 2013) - Sau, Abhijit; Santra, Abhishek; Misra, Anup Kumar
Abstract The activation of glycosyl trichloroacetimidates by nitrosyl tetrafluoroborate provides an alternative to existing protocols for the activation of these compounds in multistep oligosaccharide synthesis.